PENGARUH PENDIDIKAN KESEHATAN TERHADAP PERILAKU 3M PENCEGAHAN COVID-19 PADA IBU PKK DI DESA RAMBAH HILIR TIMUR TAHUN 2021 - Putri Wulandini; Ainil Fitri; M. Raihan Riski Ilham (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2021)
Health education is a way of supporting health programs that can produce changes and increase knowledge in a short time. This 3M behavior is said to prevent the transmission of covid-19. This study aims to find out the influence of health education on the behavior of 3M prevention of covid-19 in pkk mothers in the East Rambah Hilir Village in 2021. The design of this research uses a type of design one group pre-test post-test,Population in this study is the mother of pkk in the village of rambah downstream east. Sampling techniques in this study using sampling techniques so as to get a sample of 28 people. The research instrument uses questionnaires and observation sheets consisting of 23 questions. The results of this study showed the influence of health education on the behavior of 3M prevention covid-19 p value 0.000 < 0.05. health education can be used as a way of providing behavior for the community and it is expected that public concern and better understanding of the application of 3M behavior to the prevention of covid-19